From product system to ecosystem: How firms adapt to provide an integrated value proposition - Stonig, Joachim; Schmid, Torsten; Müller‐Stewens, Günter (Strategic Management Journal, 2022)
Abstract Research Summary Ecosystems represent a key challenge for established firms, shifting their focus from products to system‐level collaboration around integrated value propositions. This longitudinal case study of a machine manufacturer reports how an established firm created an ecosystem to enhance its focal product. Drawing on an activity system lens, we develop a model how firms can achieve fit around an integrated value proposition through mutual adaptation of product and ecosystem activities. This strategic transformation is supported by a shift towards collaborative organizational design. We elaborate on how firms can create non‐generic complementarities between products and the emerging ecosystem through product adaptations, demonstrate the role of internal and external collaboration in developing ecosystem orchestration capabilities, and highlight data generation and processing as critical factors in realizing complementarities. Managerial Summary Digital ecosystems that enable new integrated value propositions pose a challenge for established firms, as these new activities often fundamentally conflict with the existing product business. Our case study of a machine manufacturer shows how a firm can leverage its product‐focused activities to establish itself as an ecosystem leader through the mutual adaptation of its product and ecosystem activities. The focal firm modularized its products and enhanced their information‐processing capacities while simultaneously embedding them in an integrative platform with open interfaces for partner components. The firm was thus able to realize data‐driven complementarities between the platform and its components. Supporting the ecosystem‐creation process required a shift of the organizational design towards collaboration, both internally and with partners.